2013
DOI: 10.4161/auto.25190
|View full text |Cite
|
Sign up to set email alerts
|

STUB1/CHIP is required for HIF1A degradation by chaperone-mediated autophagy

Abstract: The transcription factor hiF1 is mostly regulated by the oxygen-dependent proteasomal degradation of the labile subunit hiF1A. recent data showed degradation of hiF1A in the lysosome through chaperone-mediated autophagy (cMA). however the molecular mechanism involved has not been elucidated. This study shows that the KFerQ-like motif, that has been identified in all cMA substrates, is required to mediate the interaction between hiF1A and the chaperone hSpA8. Moreover, mutations in the KFerQ-like motif of hiF1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
160
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 63 publications
(73 reference statements)
5
160
1
2
Order By: Relevance
“…Mechanisms by which HIF-1α is regulated in an O 2 -independent manner have also been identified (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In addition to proteasome-dependent pathways for HIF-1α degradation, we identified a pathway by which HIF-1α can be targeted for lysosomal degradation through chaperonemediated autophagy (27), which subsequently was confirmed by others (28)(29)(30).…”
supporting
confidence: 66%
“…Mechanisms by which HIF-1α is regulated in an O 2 -independent manner have also been identified (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In addition to proteasome-dependent pathways for HIF-1α degradation, we identified a pathway by which HIF-1α can be targeted for lysosomal degradation through chaperonemediated autophagy (27), which subsequently was confirmed by others (28)(29)(30).…”
supporting
confidence: 66%
“…Recent studies have demonstrated that CMA is activated during hypoxia and this activation is required for cell survival [38]. Although the specific substrates degraded by CMA under these conditions are not fully elucidated, the fact that the hypoxia-inducible factor 1 has been confirmed as a CMA substrate [39] supports a possible regulatory effect of CMA on the intensity and duration of the cellular response to hypoxia.…”
Section: What Are the Physiological Functions Of Cma?mentioning
confidence: 99%
“…5 Interestingly, the E3 ligase STIP1 homology and U-box containing protein 1 (STUB1, also known as CHIP), but not VHL, was shown to be required for CMA-mediated HIF1a degradation. 6 Furthermore, STUB1 mediated K63 ubiquitination in an oxygen-independent manner and was required for HIF1a degradation via CMA. 7 We identified a canonical KFERQ motif (LDKFQ) and a putative KFERQ motif (QVKVY, if Y gets phosphorylated) in human HIF2a, which raises the possibility that CMA also mediates HIF2a degradation in a similar manner.…”
mentioning
confidence: 99%